2016
DOI: 10.1186/s12864-016-3177-1
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic sex determination in the cichlid fish Astatotilapia burtoni

Abstract: BackgroundThe East African riverine cichlid species Astatotilapia burtoni serves as an important laboratory model for sexually dimorphic physiology and behavior, and also serves as an outgroup species for the explosive adaptive radiations of cichlid species in Lake Malawi and Lake Victoria. An astounding diversity of genetic sex determination systems have been revealed within the adaptive radiation of East African cichlids thus far, including polygenic sex determination systems involving the epistatic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 92 publications
(132 reference statements)
3
81
0
Order By: Relevance
“…It has been suggested that teleost karyotypes have remained largely stable since the fish-specific whole genome duplication more than 300 million years ago [34]. This is in contrast to recent reports of chromosomal fusions among closely related cichlid species [35][36][37], and a large number of putative inversions associated with the evolution of sex chromosomes in various species [13,31,38]. Chromosomescale assemblies of cichlids allow us to quantify the levels of synteny among teleost lineages, and the rate of intra-chromosomal rearrangement among cichlid lineages in East Africa.…”
Section: Introductionmentioning
confidence: 71%
“…It has been suggested that teleost karyotypes have remained largely stable since the fish-specific whole genome duplication more than 300 million years ago [34]. This is in contrast to recent reports of chromosomal fusions among closely related cichlid species [35][36][37], and a large number of putative inversions associated with the evolution of sex chromosomes in various species [13,31,38]. Chromosomescale assemblies of cichlids allow us to quantify the levels of synteny among teleost lineages, and the rate of intra-chromosomal rearrangement among cichlid lineages in East Africa.…”
Section: Introductionmentioning
confidence: 71%
“…Roberts et al. (2016), using a laboratory strain that is very likely from the same source population as the one from the University of Texas (HHL), also identified a XX/XY system on LG5 but an additional ZZ/ZW on LG13. Behavioral differences between the HH laboratory strain and southern populations (LZL and KA3) were observed in a study on maternal care (Renn et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies dealing with the genomics of sex determination in A. burtoni, Böhne et al (2016) inferred a XX/XY system located on LG5 for the laboratory strain of the University of Basel (LAB), and a XX/XY system at LG18 for a wild population from the southern lineage (KAL). Roberts et al (2016), using a laboratory strain that is very likely from the same source population as the one from the University of Texas (HHL), also identified a XX/XY system on LG5 but an additional ZZ/ZW on LG13. Behavioral differences between the HH laboratory strain and southern populations (LZL and KA3) were observed in a study on maternal care (Renn et al, 2009).…”
Section: Interestingly In Both the Southern And The Northern Clades Ofmentioning
confidence: 98%
“…234 235 Sex determination in vertebrates is highly variable with the major exceptions of Eutherian 236 mammals and birds in which XX/XY and ZZ/ZW monofactorial sex determination systems 237 have been conserved over a long evolutionary period [45,46]. In contrast, fish exhibit much 238 more diverse and dynamic sex determination [9,10,47], with monofactorial and polyfactorial 239 [48,49] genetic systems and frequent switches and turnovers of master sex-determining genes 240 [12,14,15,17,21,50]. In goldfish, we identified male-specific markers and obvious male-241 specific SNPs strongly enriched on LG22.…”
Section: Discussion 188mentioning
confidence: 99%